2017
DOI: 10.4254/wjh.v9.i9.469
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 as a biomarker for hepatocellular carcinoma in Egyptian patients

Abstract: AIMTo investigate the clinical utility of serum annexin A2 (ANXA2) as a diagnostic marker for early hepatocellular carcinoma (HCC).METHODSThis study was performed in HCC Clinic of Ain Shams University Hospitals, Cairo, Egypt and included: Group 1: Fifty patients with early stage HCC (Barcelona Clinic Liver Cancer stage A); Group 2: Twenty five patients with chronic liver disease; and Control Group: Fifteen healthy, age- and sex-matched subjects who were seronegative for viral hepatitis markers. The following l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…However, no significant correlation was noted between annexin level and other parameters. There was no significant correlation between ANXA2 level and AFP; this agrees with the studies done by El-Gezawy et al [18], Shaker MK et al [24], and Sun et al [13]. The correlation coefficient between serum ANXA2 and AFP values was not significant, indicating that measuring both markers (AFP and ANXA2) in serum can improve the diagnostic value.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, no significant correlation was noted between annexin level and other parameters. There was no significant correlation between ANXA2 level and AFP; this agrees with the studies done by El-Gezawy et al [18], Shaker MK et al [24], and Sun et al [13]. The correlation coefficient between serum ANXA2 and AFP values was not significant, indicating that measuring both markers (AFP and ANXA2) in serum can improve the diagnostic value.…”
Section: Discussionsupporting
confidence: 87%
“…These results are compatible with El-Gezawy et al who pastulated that ANXA2 was significantly higher in early HCC patients than cirrhotic patients [18]. Shaker et al also reported that ANXA2 was significantly higher in early HCC patients than chronic liver disease (CLD) patients [24]. Interestingly, in the HCC group, there was significant positive correlation between ANXA2 level and alkaline phosphatase and there was significant relation as regards fatigue, abdominal pain, and vomiting.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, 30% HCC patients present with normal AFP. Thus, they needed for new tumor markers that can differentiate between HCC and benign hepatic lesions and this is very important for early surveillance and specific diagnosis of HCC (Salim et al, 2009;Shaker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other cases AFP levels were characterized with sensitivity and specificity when tumor size is more than 3 to 5 cm in hepatocellular carcinoma (HCC) (Abdo et al, 2012;Flores and Marrero 2014). Therefore, the identification of new biomarkers with high sensitivity and specificity than AFP could be helpful in early diagnosis of Hepatocellular carcinoma (HCC) (Gish 2014;Shaker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous biomarkers had been proposed to predict earlystage HCC as well as AFP-negative HCC patients such as desgamma-carboxy prothrombin (DCP) (also known as Prothrombin Induced by Vitamin K Absence II: PIVKA II), Lens culinaris-agglutinin-reactive fraction of AFP (AFP-L3) [34], Glypican-3 (GPC3) [35], fucosylated haptoglobin [36], fucosylated paraoxonase 1 (FUC-PON1) [37]; Heat shock proteins (HSP70) [38], Annexin A2 (ANXA2) [39], microRNAs panel (miRNAs) [40], Eag1 channels [41], Transforming Growth Factor-Beta [42], Osteopontin (OPN) [43] and CAP2 [32,33]. The combination of PIVKA-II, the sensitivity of which was 48.9% in HCC patients, with AFP or AFP-L3 significantly improved its diagnostic performance [34].…”
Section: Discussionmentioning
confidence: 99%